Adapting (4,4) Networks through Substituent Effects and Conformationally Flexible 3,2’:6’,3”-Terpyridines - Dalila Rocco (MDPI AG, 2021)
Coordination networks formed between Co(NCS)2 and 4’-substituted-[1,1’-biphenyl]-4-yl-3,2’:6’,3”-terpyridines in which the 4’-group is Me (1), H (2), F (3), Cl (4) or Br (5) are reported. [Co(1)2(NCS)2]n·4.5nCHCl3, [Co(2)2(NCS)2]n·4.3nCHCl3, [Co(3)2(NCS)2]n·4nCHCl3, [Co(4)2(NCS)2]n, and [Co(5)2(NCS)2]n·nCHCl3 are 2D-networks directed by 4-connecting cobalt nodes. Changes in the conformation of the 3,2’:6’,3”-tpy unit coupled with the different peripheral substituents lead to three structure types. In [Co(1)2(NCS)2]n·4.5nCHCl3, [Co(2)2(NCS)2]n·4.3nCHCl3, [Co(3)2(NCS)2]n·4nCHCl3, cone-like arrangements of [1,1’-biphenyl]-4-yl units pack through pyridine…arene π-stacking, whereas Cl…π interactions are dominant in the packing in [Co(4)2(NCS)2]n. The introduction of the Br substituent in ligand 5 switches off both face-to-face π-stacking and halogen…π-interactions, and the packing interactions are more subtly controlled. Assemblies with organic linkers 1–3 are structurally similar and the lattice accommodates CHCl3 molecules in distinct cavities; thermogravimetric analysis confirmed that half the solvent in [Co(3)2(NCS)2]n·4nCHCl3 can be reversibly removed.